1997
DOI: 10.1073/pnas.94.23.12509
|View full text |Cite
|
Sign up to set email alerts
|

Multiple imprinted sense and antisense transcripts, differential methylation and tandem repeats in a putative imprinting control region upstream of mouse  Igf2

Abstract: The mouse insulin-like growth factor 2 (Igf2) locus is a complex genomic region that produces multiple transcripts from alternative promoters. Expression at this locus is regulated by parental imprinting. However, despite the existence of putative imprinting control elements in the Igf2 upstream region, imprinted transcriptional repression is abolished by null mutations at the linked H19 locus. To clarify the extent to which the Igf2 upstream region contains autonomous imprinting control elements we have perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
173
2
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(181 citation statements)
references
References 30 publications
5
173
2
1
Order By: Relevance
“…In contrast we have shown that the homologous region of the human IGF2 gene (between exons 3 and 4) was unmethylated on both alleles in normal kidney and Wilms tumours. As already noted above, another region of di erential methylation (dmr 0) in the mouse Igf2 gene was recently identi®ed on the maternal allele near the mouse pseudo-exon 2 (Moore et al, 1997). We have shown that the homologous region in the human is also methylated on the maternal allele and that loss of imprinting is associated with loss of methylation from this region.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…In contrast we have shown that the homologous region of the human IGF2 gene (between exons 3 and 4) was unmethylated on both alleles in normal kidney and Wilms tumours. As already noted above, another region of di erential methylation (dmr 0) in the mouse Igf2 gene was recently identi®ed on the maternal allele near the mouse pseudo-exon 2 (Moore et al, 1997). We have shown that the homologous region in the human is also methylated on the maternal allele and that loss of imprinting is associated with loss of methylation from this region.…”
Section: Discussionsupporting
confidence: 61%
“…We have shown that relaxation of IGF2 imprinting in Wilms tumours is accompanied by loss of methylation from the maternal allele in a region spanning 2 kb of DNA located upstream of the imprinted promoter complex. This region is homologous to a region of maternal allelespeci®c methylation (dmr 0), previously identi®ed in the mouse IGF2 gene (Moore et al, 1997). Analysis of the remainder of the IGF2 gene identi®ed no other regions of di erential methylation.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…In eukaryotic cells, such RNAs are known to be mostly involved in genomic imprinting [150] and X chromosome inactivation [151]. The discovery that AS transcription is more widespread than previously thought challenges this view and suggests that dsRNA may play a more general role (or perhaps a wider role) in regulation of gene expression.…”
Section: Anti-sense Rna Expression Of Arabidopsis Set Genesmentioning
confidence: 99%
“…There is mounting evidence that non-coding (especially antisense) RNAs regulate allele-specific gene expression (reviewed in [30]). Multiple sense and antisense transcripts have been detected in the mouse Igf2 5' region, and the major antisense transcript, Igf2AS, is paternally expressed and noncoding [41]. An antisense message transcribed from a homologous region near human IGF2 encodes a putative 273-amino acid protein of unknown function [42].…”
Section: Igf2 Imprinting As a Model Of Allele-specific Repressionmentioning
confidence: 99%